THE ROLE OF SCIENCE IN HADITH CRITICISM: BETWEEN NAQD IJABI AND NAQD SALBI - Ghozali, Muhammad Alfin (LP2M Ma'had Aly Hasyim Asy'ari Pesantren Tebuireng, 2025)
The study of hadith through a scientific approach is becoming increasingly popular. One of the most important but rarely highlighted themes in this regard is the discourse of using modern scientific facts as a tool in the method of hadith criticism. Can a ḍa'īf hadith that is in accordance with scientific facts be corroborated (naqd ījābi)? Then, can an allegedly authentic hadith be weakened if it contradicts modern scientific findings (naqd salbī)? These two important questions—which are the main foundations of hadith criticism through modern scientific facts—have rarely been taken seriously. In this journal, the author will answer these two questions, which also means that the author will dissect how the rules and limitations of science can be used as a tool in the method of hadith criticism. The result of this study is that scientific findings can be used as a tool in hadith criticism. They can be used to strengthen the status of a hadith or to weaken it. However, it does not mean that it can replace the position of conventional hadith criticism methodology which is fixated on the hadith sanad. The position of science as a tool of hadith criticism is to demand that we recorrect the sanad of a hadith whose matan contradicts the findings of science or vice versa. Moreover, the process of its application cannot be done haphazardly. There are various limitations and strict conditions that must be observed. [Kajian hadis melalui pendekatan ilmu sains kian ramai dilakukan. Salah satu tema kajian yang cukup penting namun jarang disorot dalam hal ini ialah wacana menggunakan fakta-fakta sains modern sebagai alat dalam metode kritik hadis. Apakah hadis ḍa’īf yang sesuai dengan fakta sains dapat dikuatkan statusnya (naqd ījābi)? Apakah hadis yang diduga sahih dapat dilemahkan statusnya jika menyalahi temuan ilmiah modern (naqd salbī)? Dua pertanyaan penting tersebut—yang merupakan fondasi utama kritik hadis melalui fakta sains modern—masih cukup jarang diperhatikan secara serius. Pada artikel ini, penulis menjawab dua pertanyaan tersebut, yang juga berarti penulis akan membedah seperti apa kaidah dan batasan-batasan agar ilmu sains dapat dijadikan peranti dalam metode kritik hadis. Hasil dari penelitian ini menyatakan bahwa temuan sains dapat dijadikan sebagai salah satu alat dalam metode kritik hadis. Ia dapat digunakan untuk menguatkan status suatu hadis atau melemahkannya. Namun, bukan berarti ia dapat menggantikan posisi metode kritik hadis konvensional yang terpaku pada sanad hadis. Posisi sains sebagai alat kritik hadis ialah untuk menuntut kritikus agar mengoreksi ulang sanad suatu hadis yang matannya berseberangan dengan temuan sains atau sebaliknya. Selain itu, proses pengaplikasiannya tidak bisa dilakukan secara serampangan. Ada berbagai batasan dan ketentuan ketat yang harus diperhatikan.]